ANALYSIS OF ACHIEVEMENTS OF NET ZERO CARBON EMISSIONS AS INDONESIA'S REFERENCE IN FULFILLMENT OF CLIMATE CHANGE MITIGATION COMMITMENTS - Teddy Wartono Sudinda (Jurnal Sains dan Teknologi Mitigasi Bencana, 2022)
Indonesia plans a target of reducing carbon emissions in the Nationally Determined Contribution (NDC) of 29 percent in 2030 on a business as usual basis (BAU) and 41 percent with international assistance until 2050. NDC is a measurable commitment in dealing with the threat of climate change, the main cause of which is the increasing emission of greenhouse gases. glass/GHG to the atmosphere. The composition of GHG itself is 94 percent in the form of carbon dioxide, CO2 produced by human activities. Almost all human activities contribute 75 percent to carbon emissions because their activities tend to come from the use of fossil fuels, BBF. Taking into account the source of carbon emissions is the largest of the main human activities, then to detect the amount of carbon emissions into the atmosphere is to calculate the individual carbon footprint, carbon footprint. The results of individual carbon footprint studies in several places/regions and nationally are informed as follows: in the Puspiptek Serpong Tangerang area, an individual carbon footprint of around 3.1-6.6 tons CO2e per year was obtained, in Semarang, Central Java an individual carbon footprint value of around 3.84 tCO2e per year was obtained. , Medan, North Sumatra produces what individual carbon footprint values ??are around 2.52 tCO2e per year, at the national level the calculation of individual carbon footprints is approached by dividing the total carbon emission data published by the Ministry of Environment and Forestry in the period 2010-2018 with the total population of Indonesia at that time, we get a range of figures carbon footprint from 3.40 sd. 9.29 tCO2e per year. The highest number occurred in 2015.